IMPLEMENTASI PASAL 28D UNDANG-UNDANG DASAR NEGERA REPUBLIK INDONESIA TAHUN 1945 DALAM PUTUSAN MAHKAMAH KONSTITUSI (Lex Jurnalica, 2022)
AbstractThe Constitutional Court is an institution that was established after the amendment of the 1945 Constitution. This institution acts as a guardian of the constitution as well as a guardian of the upholding of human rights in Indonesia. The purpose of this research is to find out how the Constitutional Court plays a role in upholding human rights in Indonesia and whether the Constitutional Court's decision on material testing has properly accommodated the enforcement of human rights. The research method used is the normative juridical method. This method is used to analyze the articles in the law, the Constitutional Court's decision on the judicial review of the 1945 Constitution of the Republic of Indonesia, and previously published journals. The results of this study indicate that the role of the Constitutional Court in upholding human rights in Indonesia, namely the Constitutional Court can conduct a judicial review of laws against the 1945 Constitution of the Republic of Indonesia. The Constitutional Court can revoke laws whose substance is considered to be contrary to the 1945 Constitution of the Republic of Indonesia or whose provisions are unclear. This is done by the Constitutional Court in order to avoid the threat of human rights if the contradictory or unclear regulations are still enforced. The Constitutional Court has conducted a judicial review of Article 20 paragraph (3) and Article 43 paragraph (2) of Law Number 26 of 2000 concerning the Human Rights Court. Then, based on this review, the Constitutional Court issued the Constitutional Court Decision Number 75/PUU-XIII/2015 and the Constitutional Court Decision Number 18/PUU-V/2007. Although the two articles were at least tested with the same articles as a touchstone, the Constitutional Court gave a different decision on the two material tests. The Constitutional Court cannot immediately grant the petition of the applicant who feels that his constitutional rights have been violated because the Constitutional Court always bases every decision on the constitution, although sometimes the Court is considered to have ruled out human rights Keywords: Human Rights, Constitutional Court, Judicial Review. AbstrakMahkamah Konstitusi merupakan lembaga yang dibentuk setelah amandemen UUD 1945. Lembaga ini berperan sebagai pengawal konstitusi (guardian of the constitution) sekaligus sebagai pengawal tegaknya Hak Asasi Manusia di Indonesia. Penulisan penelitian ini bertujuan untuk mengetahui bagaimana MK berperan dalam menegakkan HAM di Indonesia serta apakah Putusan MK atas pengujian materiil telah mengakomodasi penegakan HAM dengan tepat. Metode penelitian yang digunakan adalah metode yuridis normatif. Metode tersebut digunakan untuk menganalisis pasal-pasal dalam undang-undang, Putusan MK atas uji materiil terhadap UUD NRI 1945, dan jurnal yang telah diterbitkan sebelumnya. Hasil dari penelitian ini menunjukkan bahwa peran MK dalam menegakkan HAM di Indonesia, yaitu MK dapat melakukan uji materiil undang-undang terhadap UUD NRI 1945. MK dapat mencabut undang-undang yang substansinya dinilai bertentangan dengan UUD NRI 1945 atau tidak jelas ketentuannya. Hal tersebut dilakukan MK demi menghindari terancamnya HAM apabila peraturan yang bertentangan atau tidak jelas tersebut tetap diberlakukan. MK pernah melakukan uji materiil atas Pasal 20 ayat (3) dan Pasal 43 ayat (2) Undang-Undang Nomor 26 Tahun 2000 tentang Pengadilan HAM. Kemudian, atas pengujian tersebut MK mengeluarkan Putusan MK Nomor 75/PUU-XIII/2015 dan Putusan MK Nomor 18/PUU-V/2007. Walaupun kedua pasal tersebut setidak-tidaknya diuji dengan beberapa pasal yang sama sebagai batu uji, tetapi MK memberikan putusan yang berbeda terhadap kedua pengujian materiil tersebut. MK tidak dapat serta-merta mengabulkan permohonan pemohon yang merasa hak konstitusionalnya dilanggar karena MK selalu mendasarkan setiap putusannya pada konstitusi meskipun terkadang MK dinilai telah mengesampingkan HAM. Kata kunci: Hak Asasi Manusia, Mahkamah Konstitusi, Judicial Review.